Hubungan Pola Asuh Orangtua Terhadap Perilaku Sosial anak Usia 5-6 Tahun Di TK Kelurahan Tavanjuka - Rahma , Mutia Mifta; Agusniatih, Andi; Amrullah , Amrullah; Durrotunisa, Durrotunisa (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2025)
This study aims to examine the relationship between parenting styles and the social behavior of children aged 5-6 years at TK Kelurahan Tavanjuka, Palu City. The sample consisted of 25 children selected purposively. The research used a quantitative correlational approach with data collected through observation, questionnaires, and documentation. Results showed that 32% of parents applied an authoritarian style, 24% democratic, and 44% permissive. Regarding children’s social behavior, 8% were categorized as Very Well Developed (BSB), 25.33% as Well Developed (BSH), 49.33% as Developing (MB), and 17.33% as Not Yet Developed (BB). Children with authoritarian parenting exhibited high discipline and responsibility but low independence. In contrast, the democratic style optimally supported all three aspects, while permissive parenting was associated with lower discipline and responsibility. Spearman’s correlation analysis revealed a significant positive relationship between parenting styles and children’s social behavior (r = 0.511; p = 0.001), indicating that better parenting styles correspond to better social behavior in children. These findings emphasize the importance of balanced and responsive parenting to support early childhood social development.